THE CURRENT STATE OF STUDY OF PLANTS OF HEDYSARUM L. FLORAE OF THE CAUCASUS - D. R. Imachuyeva; F. K. Serebryanaya (Фармация и фармакология (Пятигорск))
The article presents an overview of the ecological-botanical research and the current state of knowledge of species of the genus Hedysarum L. of the legume family (Fabaceae) grown in the Caucasus.The aim of the study was the review of the information contained in open sources about the basic ecological and Botanical characteristics, geographic specie of habitat and phytocoenotic specie of species of the genus Hedysarum growing in the Caucasus.Materials and methods. The study was conducted using information retrieval (PubMed, ScholarGoogle), library databases (eLibrary, Cyberleninca, RGB, VINITI, SOCIONET, ReseachGate, PubMed, Web of Sciences, SCOPUS, RNMJ.RU, UlrichsWEB, EBSCO, Scientific library of the Botanical Institute of RAS) as well as the results of our research.Results: the review study of species of the genus Hedysarum L. of the legume family (Fabaceae) grown in the Caucasus.Conclusion: the results of the analysis of regional floras, morphological characteristics, the main ecological and botanical characteristics of these 16 species, the geographic specie of habitat, phytocenotic specie are presented.